Lightwave nano-converging enhancement by an arrayed optical antenna based on metallic nano-cone-tips for CMOS imaging detection - Chai Hu; Taige Liu; Kewei Liu; Jiashuo Shi; Mao Ye; Xinyu Zhang (Scientific Reports, 2022)
Abstract A kind of gold-coated glass nano-cone-tips (GGNCTs) is developed as an arrayed optical antenna for highly receiving and converging incident lightwaves. A local light field enhancement factor (LFEF) of ~ 2 × 104 and maximum light absorption of ~ 98% can be achieved. The near-field lightwave measurements at the wavelength of 633 nm show that the surface net charges over a single GGNCT make a typical dipole oscillation and the energy transmits along the wave vector orientation, thus leading to a strong local light field enhancement. An effective detection method by near-field coupling an arrayed GGNCT and complementary metal–oxide–semiconductor (CMOS) sensor for highly efficient imaging detection is proposed. The lightwave detection at several wavelengths, including typical 473 nm, 532 nm, 671 nm, and 980 nm, shows a notable characteristic that a better capability of the net charge distribution adjusting and localized aggregating can be obtained at the absorption peak of the GGNCT developed and a stronger signal detection achieved. The research lays a foundation for further developing a light detector with an ideal optoelectronic sensitivity and broad spectral suitability, which is based on integrating GGNCTs as an arrayed optical antenna with common sensors.